ADDRESSING GENDER INEQUALITY IN ENROLMENT AND ATTTENDANCE IN BASIC EDUCATION: THE ROLE OF NON-GOVERNMENTAL ORGANIZATIONS (NGOs) IN THE NORTHERN REGION OF GHANA - Eliasu, A. (UDS International Journal of Development, 2018)
Fundamentally, the question is no longer whether NGOs should play a role in education in Northern Region but how they are most likely to bridge the inequality gap, improve quality and access to basic education. This paper examines comprehensively whether NGOs in Northern Region have been able to provide a solution to the gender inequality gap in enrolment and attendance, the kind of relationship they have with GES and their challenges. The study was both qualitative and descriptive. Â Instruments such as interview guides, observations and semi- structured interview schedules were used to source the primary data from the selected NGO officials, the District Directors, the pupils and the teachers while the secondary data were sourced from journals, internet and published theses. The study showed that some of the activities of NGOs to address gender inequality in enrolment and attendance in the Northern Region include research on girlsâ€™ education, advocacy by using media to educate the public on the need for girlsâ€™ education, capacity building, especially training of teachers and school girls, provision of both teacher and girls incentives, formation of girlsâ€™ clubs and training of parents to be able to cope with their girlsâ€™ education. The study also showed that non-availability of data at the District Education Offices, lack of cooperation on the part of District Education officials and lack of logistics at the District Offices made it very difficult to provide a solution to the access gap in basic education by NGOs. Boys are therefore still ahead of the girls in terms of educational achievement at the basic education level in the Northern Region of Ghana. The paper calls for attitudinal change of both the GES and the NGOs assisting in basic education in the region. Â Keywords: Basic Education, Gender Gap, Inequality, Enrolment, Attendance